2022
DOI: 10.3390/su14095312
|View full text |Cite
|
Sign up to set email alerts
|

Environmental “Fee-to-Tax” and Heavy Pollution Enterprises to De-Capacity

Abstract: Will environmental “fee-to-tax”, which strengthens the rigidity of levies and increases the environmental costs of heavy pollution enterprises, force heavy pollution enterprises to de-capacity. This paper examines the impact and heterogeneity of the environmental “fee-to-tax” on heavy pollution enterprises’ de-capacity by taking the official implementation of the Environmental Protection Tax Law of the People’s Republic of China in 2018 as the institutional impact and the listed industrial enterprises in Shang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the benchmark regression, we found that the tightening of environmental regulations brought about by the environmental protection fee-to-tax policy has effectively improved the level of corporate ESR, and is more significant for firms in maturity and decline stages. This may be because, on the one hand, the institutional change from pollution charges to environmental protection taxes has led to the improvement of the legal level and the increase of tax incentives, which has prompted firms affected by the policy to improve the utilization rate of production capacity and increase environmental protection investment, thus realizing the comprehensive green transformation [7,29], which is the concrete manifestation of firms' active ESR. The conclusion is also supported by the research conclusions of other scholars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the benchmark regression, we found that the tightening of environmental regulations brought about by the environmental protection fee-to-tax policy has effectively improved the level of corporate ESR, and is more significant for firms in maturity and decline stages. This may be because, on the one hand, the institutional change from pollution charges to environmental protection taxes has led to the improvement of the legal level and the increase of tax incentives, which has prompted firms affected by the policy to improve the utilization rate of production capacity and increase environmental protection investment, thus realizing the comprehensive green transformation [7,29], which is the concrete manifestation of firms' active ESR. The conclusion is also supported by the research conclusions of other scholars.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al [28] found that the environmental protection tax has a synergistic effect on the emission reduction of air pollutants and carbon dioxide. Ji and Zeng [29] believed that the environmental fee tax reform would increase a firm's environmental pollution cost by strengthening the rigidity of tax collection and management, so as to realize the capacity reduction of heavily polluting firms. Although these studies can help us to fully understand the policy effect of environmental protection tax.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A substantial body of literature has inferred an array of positive effects of environmental taxes on firms. For instance, environmental taxes have been observed to stimulate green innovation [7,11], bolster productivity [9], spur environmental investment [15,16], improve market competitiveness [10], enhance firm performance [12], assist in de-capacities [8], and advance corporate environmental social responsibility [13].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A majority of existing studies evaluating the policy related to this environmental tax reform relied on industry-wide samples. The division between the experimental and control groups was based on whether the firms belonged to heavily polluting industries [6][7][8][9][10]. Non-polluting industries may serve as less optimal control groups, given they typically comprise sectors with minimal environmental impact, such as information technology, finance, and education.…”
Section: Introductionmentioning
confidence: 99%
“…The third batch of low-carbon pilot provinces and cities include six provinces and cities, i.e., Tianjin, Chongqing, Qinghai, Hainan, Guizhou, and Inner Mongolia Autonomous environmental regulation, EPTL can also promote energy transition. For example, studies on heavily polluting enterprises found that EPTL significantly increases the total factor productivity of heavy pollution enterprises [15], promotes green innovation [16], increases green investment [17], and gradually " de-capacity " [18] to promote its transformation. Meanwhile, EPTL incentives green mergers and acquisitions of heavy polluters in the capital market and facilitate green transformation of enterprises [19].…”
Section: Introductionmentioning
confidence: 99%